2019
DOI: 10.3390/su11020521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Energy Sector Development Trends and Forecast of Final Energy Demand in the Baltic States

Abstract: The paper provides a comparative analysis of economic growth in Estonia, Latvia and Lithuania and discusses differences in development of the main sectors during the period 2000–2016. Based on detailed analysis of energy sector development, the driving factors influencing changes in primary energy consumption in each country and in the Baltic region are discovered. Increase of renewable energy sources (RES) consumption in the Baltic region over this period by 73.6% is emphasized. The paper presents valuable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…As in the case of the BRICS, European countries were studied separately: Portugal by [84]. Portugal, Spain, Denmark and the USA by [85], Ukraine by [86,87], Turkey by [88,89], Romania by [90], Czech Republic and Slovakia by [91], Wales by [92], Poland by [93,94], Estonia, Latvia and Lithuania by [95], Scotland by [96] and Russia [97]. The American continent, to be more precise, Latin America, was also the target of research by [98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of the BRICS, European countries were studied separately: Portugal by [84]. Portugal, Spain, Denmark and the USA by [85], Ukraine by [86,87], Turkey by [88,89], Romania by [90], Czech Republic and Slovakia by [91], Wales by [92], Poland by [93,94], Estonia, Latvia and Lithuania by [95], Scotland by [96] and Russia [97]. The American continent, to be more precise, Latin America, was also the target of research by [98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major changes was seen in the patterns of demand of energy resources. The demand of oil got reduced to 37.6% from 47.3% (Miskinis et al, 2019). Use of alternate sources, exploitation and production were developed and sought.…”
Section: Fuel Substitution and Gdpmentioning
confidence: 99%
“…Based on the analysis presented by Ross et al [17], an increase in the RES share and the energy efficiency improvement were identified as the main tools for fulfilling these targets. Furthermore, the need for in-depth analysis and implementation of new policies and technological changes was revealed by Miskinis et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…To have an in-depth comparison of actual RES deployment in separate sectors, detailed data obtained from statistical offices of Estonia, Latvia and Lithuania were examined. Additionally, the harmonisation of data from national statistics was performed, considering differences in each country's energy balance construction principles, which were revealed in [18]. The harmonised data enabled us to prove their comparability across three countries and sectors of the national economies.…”
Section: Introductionmentioning
confidence: 99%